AP-2δ Expression Kinetics in Multimodal Networks in the Developing Chicken Midbrain - Kettler, Lutz; Sid, Hicham; Schaub, Carina; Lischka, Katharina; Klinger, Romina; Moser, Markus; Schusser, Benjamin; Luksch, Harald (Frontiers in Neural Circuits, 2021)
AP-2 is a family of transcription factors involved in many aspects of development, cell differentiation, and regulation of cell growth and death. AP-2δ is a member of this group and specific gene expression patterns are required in the adult mouse brain for the development of parts of the inferior colliculus (IC), as well as the cortex, dorsal thalamus, and superior colliculus. The midbrain is one of the central areas in the brain where multimodal integration, i.e., integration of information from different senses, occurs. Previous data showed that AP-2δ-deficient mice are viable but due to increased apoptosis at the end of embryogenesis, lack part of the posterior midbrain. Despite the absence of the IC in AP-2δ-deficient mice, these animals retain at least some higher auditory functions. Neuronal responses to tones in the neocortex suggest an alternative auditory pathway that bypasses the IC. While sufficient data are available in mammals, little is known about AP-2δ in chickens, an avian model for the localization of sounds and the development of auditory circuits in the brain. Here, we identified and localized AP-2δ expression in the chicken midbrain during embryogenesis. Our data confirmed the presence of AP-2δ in the inferior colliculus and optic tectum (TeO), specifically in Shepherd's Crook neurons, which are an essential component of the midbrain isthmic network and involved in multimodal integration. AP-2 expression in the chicken midbrain may be related to the integration of both auditory and visual afferents in these neurons. In the future, these insights may allow for more detailed study of circuitry and computational rules of auditory and multimodal networks.